Symbol

# Calculator search results

Formula
Solve the equation
Graph
$y = 4 \left ( 3 x + 5 \right ) - 3 \left ( 2 x - 1 \right )$
$y = 5$
$x$Intercept
$\left ( - \dfrac { 23 } { 6 } , 0 \right )$
$y$Intercept
$\left ( 0 , 23 \right )$
$4\left(3x+5\right)-3\left(2x-1\right)=5$
$x = - 3$
 Solve a solution to $x$
$\color{#FF6800}{ 4 } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 3 } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) = \color{#FF6800}{ 5 }$
 Organize the expression 
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 18 }$
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 18 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 3 }$
$x = - 3$
Solve the fractional equation
$\color{#FF6800}{ 4 } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 3 } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) = \color{#FF6800}{ 5 }$
 Solve a solution to $x$
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 3 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture